Different Individuals Named Khunes in the Cataract Region - Jiménez-Serrano, Alejandro (Zeitschrift für ägyptische Sprache und Altertumskunde, 2013)
The main aim of this paper is to analyze the epigraphic data which contains the name of Khunes, recently enriched with some inscriptions from the island of Sehel. One of the texts can surely be dated to the reign of Pepy I. This has provoked some confusion among scholars with regard to chronology. Most of the inscriptions contain the name of Khunes, and these were identified with a single individual who should have been lived under the reign of Pepy I, Merenre and Pepy II. This identification has not taken into account the different titles mentioned. In this context, tomb nº 34h at Qubbet el-Hawa, prepared for a high official of Elephantine called Khunes, emerges as an important element in the chronological debate, given that it cannot be dated to before the end of Pepy II’s reign.